A Qualitative Study Investigating the Onboarding Experience in Higher Education and the Effect that It Has on Employment Retention, Satisfaction, and Success - Queen, Jaclyn (My University, 2024)
Orientation programs have traditionally been implemented to share information about the institution and typically involve consistent goals that connect new faculty to other colleagues, clarify and establish expectations, expose new faculty to the culture of the institution, and introduce each to the available services at the institution. Historically, new faculty orientation programs have struggled to clarify their role and purpose and develop programs that meet each person’s specific needs. This study investigates the effectiveness and significance of new faculty orientation programs at Georgia College & State University and Valdosta State University, focusing on the perceptions and experiences of each of the 13 new faculty who participated in the study during the 2022-2023 academic year. The study explores activities, challenges, and insights related to onboarding, aiming to understand its impact on new faculty. Specifically, this study examines how onboarding and orientation practices impact newly hired faculty members' integration, sense of belonging, long-term engagement, and uncertainty reduction within their institution. The study highlights the importance of tailored orientation practices in clarifying expectations and connecting faculty with campus resources. Key factors contributing to successful onboarding include personalized experiences, valuable connections, and clear communication of institutional values. Findings from the interviews reveal the significance of orientation programs in fostering community integration and readiness for academic roles and suggest that effective onboarding facilitates and enhances immediate engagement, a sense of belonging, and long-term retention and presents the significance and role of orientation programs in an important introduction to the academic community.
Keywords: Education; Dissertations, Academic--United States; Georgia; College teachers--Orientation; College teachers; Employee orientation--Georgia; College teachers--Job satisfaction; Organizational change--Social aspects; Employee motivation; Mentoring in education; Valdosta State University; Case studies; Qualitative research; Universities and colleges--Faculty; College teachers--Recruiting